SYARAH HADIS DALAM BENTUK FILM: STUDI SYARAH HADIS â€˜KEUTAMAAN SALAT SHUBUHâ€™ DALAM FILM â€œCINTA SHUBUHâ€ - HS, Muhammad Alwi; Faizah, Fatikhatul (IAIN Ponorogo, 2020)
Abstract: This article aims to show the important role (contribution) of the film world in grounding the teachings of Islam through the sharah of hadith in the modern era (millennial), in this case it will focus on the film